2006
DOI: 10.1103/physreva.73.033812
|View full text |Cite
|
Sign up to set email alerts
|

Quantum manipulation of two-color stationary light: Quantum wavelength conversion

Abstract: We present a quantum manipulation of a traveling light pulse using double atomic coherence for two-color stationary light and quantum frequency conversion. The quantum frequency conversion rate of the traveling light achieved by the two-color stationary light phenomenon is near unity. We theoretically discuss the two-color stationary light for the frequency conversion process in terms of pulse area, energy transfer and propagation directions. The resulting process may apply the coherent interactions of a weak … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 19 publications
(35 reference statements)
0
61
1
Order By: Relevance
“…Recently it has been shown that the simultaneous presence of two counter-propagating control fields of comparable strength can lead to a quasi-stationary pattern of slow light consisting of two counter-propagating probe field components [7,8,9,10]. Such stationary light pulses hold particular interest as examples of efficient nonlinear optical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that the simultaneous presence of two counter-propagating control fields of comparable strength can lead to a quasi-stationary pattern of slow light consisting of two counter-propagating probe field components [7,8,9,10]. Such stationary light pulses hold particular interest as examples of efficient nonlinear optical processes.…”
Section: Introductionmentioning
confidence: 99%
“…EIT allows to transmit a resonant probe beam through an otherwise opaque atomic medium coherently driven by a control laser field and forms the basis of many interesting applications as e.g. creating stationary excitations of light [33][34][35][36][37] in more complex double Λ schemes as shown in Fig. 1b, Bose-Einstein condensation of photons [36,38], or artificial magnetic fields [37,39] for photons.…”
Section: Introductionmentioning
confidence: 99%
“…Employing two pairs of counterpropagating beams involves two atomic coherences leading to the SSL. By applying the secular approximation [33,34], the SSL has been shown to obey an effective 1D Dirac equation [45]. This approximation is however only justified in hot atomic gases [8,46], because it neglects all higher wave-vector components of the atomic coherence produced by the counterpropagating beams driving the same transition.…”
Section: Introductionmentioning
confidence: 99%
“…Later analysis showed that counter-propagating control fields of very different frequencies can also give rise to SL. The explanation is that shape-preserving EIT propagation in both directions can add up to prevent propagation [23,24]. In fact, true standing wave control fields can cause unwanted coupling between counter-propagating fields and additional decay of the SL pulse [25,26,27,28].…”
mentioning
confidence: 99%